2021
DOI: 10.5114/ada.2020.95655
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of illness and need for education to support dermatology self-care in psoriasis patients: a cross-sectional study

Abstract: Introduction Acceptance of illness greatly affects the quality of life of psoriatic patients. Assessment of patients’ need for education and support is very important for patients’ counselling and follow-up. Aim To evaluate acceptance of illness and need for education to support dermatology self-care in Arabic patients with psoriasis. Material and methods A cross-sectional study using a survey was conducted. The survey collected patients’ dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Contrary to this finding, Soliman (24) found that psoriasis patients reported that the feet, toes, and toenails was the least affected parts however, the scalp and hairline was the highest affected area. Additionally, the results of present study showed that only a minority of patients had clear or non-inflamed psoriasis plaques, whereas almost two-fifths of patients reported very red, inflamed, scaly, or thick plaques which is similar to the findings of Soliman (29) .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Contrary to this finding, Soliman (24) found that psoriasis patients reported that the feet, toes, and toenails was the least affected parts however, the scalp and hairline was the highest affected area. Additionally, the results of present study showed that only a minority of patients had clear or non-inflamed psoriasis plaques, whereas almost two-fifths of patients reported very red, inflamed, scaly, or thick plaques which is similar to the findings of Soliman (29) .…”
Section: Discussionsupporting
confidence: 87%
“…Controversy, the study of Kowalewska et al (34) concluded that the level of psoriasis acceptance among men was significantly higher than among women. Besides that, Soliman (29) and the Egyptian study of Aladi et al (40) showed that psoriasis acceptance did not differ in relation to gender.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This justifies level of acceptance of illness to be an important element in the quality of life of patients and a self-rated health of patients [ 40 , 41 ]. Therefore, to add an important element in the holistic medical or nonmedical care, educating epileptic patients about their chronic disease might be essential to increase patients' level of acceptance of illness and thereby increase their quality of life [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%